Integrating Digital Tools in ELT: Evaluating English Skills through Mobile-Based Assessment Platform - Azizah Maulina Erzad; Nuskhan Abid (English Department - University of Sultan Ageng Tirtayasa, 2025)
Integrating mobile technology into English Language Teaching (ELT) has created new opportunities for enhancing students’ language proficiency through flexible and accessible application. This study aimed to investigate the extent to which the EnglishScore application is beneficial for improving English language skills, the challenges users encounter while using the application, and its potential future applications in developing English language skills. Based on a qualitative design, data were gathered through observations and a questionnaire. The participants were EFL students who had used EnglishScore as a part of their learning activities at an Islamic university in Indonesia. The findings revealed that students view the application as helpful for improving their language skills, especially in reading comprehension, grammar, and listening. Students also reported increased confidence and familiarity with English tests after using the app. Despite minor challenges such as unfamiliar vocabulary and internet connection issues, the overall responses indicate a positive attitude toward mobile-based assessment tools. This study implies that mobile apps like EnglishScore can provide a supportive complement to formal language instruction and promote learner autonomy in higher education contexts. Future studies are recommended to utilize mixed-method approaches to examine the long-term effects of such tools on varying levels of English proficiency.